Outcome of Total Knee Arthroplasty with Insall Burstein-II Prosthesis (Medical Forum Monthly, 2024)
Objective: Evaluate the functional outcome of total knees arthroplasty with IB II prosthesis and evaluate the alignment of prosthetic components by radiological parameters and its conflation with functional outcome.Study Design: Descriptive / case series studyPlace and Duration of Study: This study was conducted at the Orthopaedic Surgery at Shaikh Zayed Hospital, Lahore from 1st September 2006 to 31st August 2009.Subject and Methods: Sixty knees of sixty patients were replaced by using Insall Burstein II prosthesis postoperative radiographs were evaluate for alignment of knee and prosthesis components by criteria selected from knee society Roentogenographic evaluation system. Functional outcome from evaluated by rationale of knee society knee rating system.Results: Prosthesis component was aligned in 93% and mail-alignment in 7% of the cases. There was significant improvements in function score 33.8±315.5 to 59.5±17.7 and knee score from 3±712.5 to 76.4±2.2. Postoperative functional score was found correlated with alignment significantly.Conclusion: Total knee arthroplasty with 1-B-II prosthesis is safe durable and predictable procedure with proper surgical technique and expertise good alignment and satisfactory functional outcome can be achieved.